THE RELATIONSHIP BETWEEN CORPORATE GOVERNANCE STRUCTURE AND THE LEVEL OF VOLUNTARY DISCLOSURE - Arifin, Arifin (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2003)
This study investigates the relationship between Corporate Governance Structure (i.e. board of directors composition and the audit committee) and the level of voluntary disclosures in the annual reports of Indonesian manufacturing public-listed companies. Voluntary disclosure items were determined by observing information presented in annual reports and by referring to a large number of voluntary items found by previous researchers in other countries. These voluntary items were then compared to the Indonesian Accounting Standard and the Capital Market Executive Agency's (BAPEPAM) regulations. From discussions with accounting and finance professionals, a final list consisting of 58 voluntary items were derived. The level of voluntary disclosure is measured cross sectionally for 1999 annual reports using a weighted disclosure index formula. The empirical evidence suggests that the board of director's composition and firm size (as an additional variable) are statistically related to the level of voluntary disclosure. In contrast, the presence of audit committee does not appear to be an important factor in explaining voluntary disclosure level of companies. Arguably, this study makes a positive contribution to the existing research in voluntary disclosures from the perspective of a developing country and that it has provided an interesting dimension to the literature of international accounting.